Disability and Multi-Dimensional Quality of Life: A Capability Approach to Health Status Assessment - Paul Anand; Laurence Roope; Anthony J. Culyer; Ron P. Smith (Institute of Labor Economics (IZA), 2019)
This paper offers an approach to assessing quality-of-life, based on Sen's (1985) theory, which it uses to understand loss in quality-of-life due to mobility-impairment. Specifically, it provides a theoretical analysis which is able to account for the possibility that some functionings may increase when a person's capabilities decrease, if substitution effects are large enough. We then develop novel data consistent with our theoretical Senian framework that permits comparison of quality-of-life between those with a disability (mobility-impairment) and those without. Empirical results show that mobility impairment has widespread rather than concentrated impacts on capabilities and is associated with higher psychological costs.. We also find evidence that a small number of functionings are higher for those with a disability, as our theory allows. The paper concludes by discussing possible implications for policy and health assessment methods.
Keywords: D60; I31; 330; mobility impairment; disability; capabilities; health; Sen; extra-welfarism